Rechargeable Aqueous Aluminum Organic Batteries. (28th January 2021) - Chen, Jiangchun; Zhu, Qiaonan; Jiang, Li; Liu, Rongyang; Yang, Yan; Tang, Mengyao; Wang, Jiawei; Wang, Hua; Guo, Lin
Abstract: Aqueous aluminum‐ion batteries (AABs) are regarded as promising next‐generation energy storage devices, and the current reported cathodes for AABs mainly focused on inorganic materials which usually implement a typical Al 3+ ions (de)insertion mechanism. However, the strong electrostatic forces between Al 3+ and the host materials usually lead to sluggish kinetics, poor reversibility and inferior cycling stability. Herein, we employ an organic compound with redox‐active moieties, phenazine (PZ), as the cathode material in AABs. Different from conventional inorganic materials confined by limited lattice spacing and rigid structure, the flexible organic molecules allow a large‐size Al‐complex co‐intercalation through reversible redox active centers (‐C=N‐) of PZ. This co‐intercalation behavior can effectively reduce desolvation penalty, and substantially lower the Coulombic repulsion during the ion (de)insertion process. Consequently, this organic cathode exhibits a high capacity and excellent cyclability, which exceeds those of most reported electrode materials for AABs. This work highlights the anion co‐intercalation chemistry of redox‐active organic materials, which is expected to boost the development of high‐performance multivalent‐ion battery systems. Abstract : A highly rechargeable aqueous aluminum‐organic battery system based on phenazine has been developed. The phenazine cathode undergoes a reversible electrochemical redox with high structural stability to accommodate the large‐size aluminum‐complex ions (de)insertion, and shows a strikingly stable aluminum storage capacity for promising large‐scale energy applications.